Behavioral Ecology of the Coffee White Stem Borer: Toward Ecology-Based Pest Management of India's Coffee Plantations - Rajus, Santosh; Bhagavan, Sriraksha G.; Kharva, Hinal; Rao, Srinivas; Olsson, Shannon B. (Frontiers in Ecology and Evolution, 2021)
India is the seventh largest producer of coffee with 395,000 tonnes of coffee exports that earn 10 billion US dollars annually. Two varieties of coffee are grown in India, Coffea arabica (arabica) and Coffea canephora (robusta). Xylotrechus quadripes, commonly known as Coffee White Stem Borer (CWSB), is a major pest of arabica, causing yearly crop damage of 17-40 million dollars. Management strategies, over 100 years in development, have provided successful, yet inconsistent solutions due to differences in local climate, elevation, natural enemies, grower diligence, and other factors. In addition, increased pesticide use affects both pests as well as their natural enemies, which has severe negative impacts on the biodiverse regions where coffee is grown. As a result, our goal is to develop an ecology-based solution for long term management of CWSB that reduces the use of pesticides and focuses on the importance of natural enemies and native hosts. In situ behavioral experiments were performed to examine the preferences of CWSB for various local species under field conditions. We found that CWSB beetles were attracted to both healthy arabica and robusta plants, and host plant volatiles played a key role in host selection. In addition, the beetles were attracted to the leaves of these coffee plants and also 2 species of cut stems from common shade trees; Spathodea campanulata (nandi flame) and Grevillea robusta (silver oak). Beetles were not attracted towards cut stems of Tectona grandis (teak) or Coffea arabica. GC-EAD and EAG experiments were then performed to identify host plant volatiles for these species, and these compounds were tested in field conditions to assess their effectiveness against the known chemical attractant pheromone. We found that the CWSB was attracted to our identified host volatile blend as much as the pheromone lure, although trap catches in general were very low. Having an understanding of the behavioral ecology of this pest can form the basis for new methods that use natural attractant and repellent plants to control the pests, reduce the cost of plantation pest management, and avoid the extensive use of insecticides.